The Arab Ethnic Identity Politics in Indonesia: A Female Representation in Fatat Qarut and Fatimah - Amsariah, Siti; Al-Bahar, Ali Hasan; Ummah, Sayidatul (Buletin Al-Turas, 2024)
PurposeThis research sought to delve into the representation of Arab women in 'Fatat Qarut' and 'Fatimah' as well as conducting a comparative analysis upon the textual ideologies instilled in both works.MethodThis research was a qualitative study utilizing descriptive analysis. A documentation technique was used as data collection means concentrating on specific passages within the text in order to uncover the strategies employed in representing women through textual quotations. Technically, the quotations were analysed using a comparative literature framework and feminist literary criticism. FindingsThis research demonstrated that the two texts present different portrayals of women based on the narrative strategy used. This variance was attributed to the generational gap between the two authors. 'Fatat Qarut' depicts women as superior and independent, whereas 'Fatimah' portrays women as inferior and submissive. ConlcusionThe study conlcudes these depictions highlight that the role and status of women within the Arab ethnic group are shaped and dominated by social and cultural stratification.